Comparision of several secondary metabolite and elemental ion contents of leaves from Kandelia obovata and Sonneratia caseolaris forests located in the Red River delta - Loan, Nguyen Thi Ngoc; Tan, Dao Van; Huyen, Tran Thi Thanh; Quang, Nguyen Hong; Hue, Le Thi Van; Nga, Pham Thi Thanh; Quinn, Claire; Carrie, Rachael; Stringer, Lindsay; Hackney, Chris (Academia Journal of Biology, 2020)
The two mangrove species Kandelia obovata and Sonneratia caseolaris were widely planted in the Red River delta. Both K. obovata and S. caseolaris forests play an important role in the economic development and environmental protection of the delta. However, chemical responses of the common mangrove forests to different ecological conditions in the delta have not yet been described. In this study, we evaluated chemical responses of K. obovata and S. caseolaris through comparisons of the content of metabolites and element ions in leaves of mangrove plants located under different ecological conditions in the Red River delta. In the low salinity area (Thuy Truong), specific leaf areas of K. obovata and S. caseolaris were much lower while the succulent index was higher compared to those in the high salinity area (Kim Trung). In Kim Trung, both species had a lower ratio of chlorophyll a/chlorophyll b. K. obvata in lower light (under the S. caseolaris canopy) had lower levels of chlorophyll b, resulting in a higher Chla/chlb ratio. There was no difference in the Mg content of leaves between two areas. An increase in Na content in leaves of mangrove plants in the higher salinity area was evident. The high K/Na ratio in leaves were eveluated for both species in high salinity areas. Our results also showed better uptake of K in leaves of S. caseolaris growing in the low salinity conditions (Thuy Truong), i.e. Thuy Truong has more favourable ecological conditions for S. caseolaris. Carotenoid contents in leaves of both species growing in the higher salinity were lower.